ECONOMIC HARDSHIP AND POST-BASIC EDUCATION AND CAREER DEVELOPMENT (PBECD) IN NIGERIA - Charity, Dafiaghor; Eguonor , Temienor; Jane Ndidiamaka , Nnorom (PT. Antis International Publisher, 2024)
Objective: To examine the impact of economic hardship on teachers’ job performance and students’ academic performance in Post-Basic Education and Career Development (PBECD) in Nigeria. Method: This paper is a review paper that depends on secondary data which were collected from relevant books, seminar papers, workshop papers, articles, etc. Results: Economic hardship has affected teachers’ job performance and students’ academic performance in Post-Basic Education and Career Development (PBECD) in Nigeria. Economic hardship has also affected the management of Post-Basic Education and Career Development (PBECD) in Nigeria. Novelty: The paper recommends that governments should increase the salaries of teachers in Post-Basic Education and Career Development (PBECD), provide bursaries and scholarships for students, increase the budgetary allocation for PBECD schools, and provide school buses to transport both teachers and students to their respective schools.